THE STRATEGY IMPROVING SCHOOL-BASED ENTERPRISE: AN ANALYTIC HIERARCHY PROCESS APPROACH IN VOCATIONAL SCHOOL - Arie Wibowo Khurniawan; Illah Sailah; Pudji Muljono; Bambang Indriyanto; Mohamad Syamsul Maarif (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aimed to design a strategy to increase a vocational school-based enterprise's effectiveness by implementing school governance (SG) and total quality management (TQM). The study is a quantitative research using the Analytic Hierarchy Process (AHP) approach to determine the appropriate strategy. The research subjects involved seven experts from the Director of Vocational High Schools of the Ministry of Education and Culture of Indonesia, the principal of Vocational School of DKI Jakarta and East Java Provinces, representatives of the Indonesian Ministry of Home Affairs, practitioners of vocational school-based enterprises, NGOs Care for vocational schools, and industry practitioners. The expert judgment used a pairwise comparison questionnaire, and then the analysis is carried out using Expert Choice V11 software. The AHP approach starts with determining the objectives, criteria, attributes, and alternatives offered. It was revealed that the School Governance strategy is the best alternative in increasing school effectiveness for the vocational school-based enterprise. The improvement of effectiveness school-based enterprise should consider implementing school governance, and it will be increased by the total quality management application. The strategy using school governance and total quality management to increase the effectiveness of the vocational school, especially at vocational school with school-based enterprise status in Indonesia